Deaths in triathletes: immersion pulmonary oedema as a possible cause. Issue 1 (29th August 2016) - Moon, Richard E; Martina, Stefanie D; Peacher, Dionne F; Kraus, William E
Abstract : Background/aim: To address the question as to whether immersion pulmonary oedema (IPO) may be a common cause of death in triathlons, markers of swimming-induced pulmonary oedema (SIPO) susceptibility were sought in triathletes' postmortem examinations. Methods: Deaths while training for or during triathlon events in the USA and Canada from October 2008 to November 2015 were identified, and postmortem reports requested. We assessed obvious causes of death; the prevalence of left ventricular hypertrophy (LVH); comparison with healthy triathletes. Results: We identified 58 deaths during the time period of the review, 42 (72.4%) of which occurred during a swim. Of these, 23 postmortem reports were obtained. Five individuals had significant (≥70%) coronary artery narrowing; one each had coronary stents; retroperitoneal haemorrhage; or aortic dissection. 9 of 20 (45%) with reported heart mass exceeded 95th centile values. LV free wall and septal thickness were reported in 14 and 9 cases, respectively; of these, 6 (42.9%) and 4 (44.4%) cases exceeded normal values. 6 of 15 individuals (40%) without an obvious cause of death had excessive heart mass. The proportion of individuals with LVH exceeded the prevalence in the general triathlete population. Conclusions: LVH—a marker of SIPO susceptibility—was present in a greater than the expected proportion of triathletes who died during the swim portion. We propose that IPO may be a significant aetiology of death during the swimming phase in triathletes. The importance of testing for LVH in triathletes as a predictor of adverse outcomes should be explored further.